Instructors' perspective on e-learning adoption in Sri Lanka: a preliminary investigation - Mohamed, Tawfeek; Hussin, Husnayati (IBIMA Publishing, 2008)
E-Learning has become an increasingly popular mode of instruction in higher education due to advances in the Internet and multimedia technologies. The purpose of the study is to gauge the perception and views of the lecturers at South Eastern University (SEUSL). As it is an exploratory study, the case study method was undertaken. The result of the study indicates that the lecturers are with positive attitude and supportive mindset to embark on e-learning initiative and it also identified a number of factors that could potentially influence the e-learning implementation in the university. Moreover the findings are instrumental and directing in undertaking a comprehensive study to understand the overall perception of lecturers towards e-learning implementation at the tertiary educational institutions in Sri Lanka.